2020
DOI: 10.1007/s10876-020-01758-y
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Studies of Zn12O12 Clusters Doped with Mg/Eu and Defect Complexes

Abstract: We report a density functional theory study of ZnO cluster doped with Eu and Mg along with native point defects using the generalized gradient approximation including the Hubbard parameter. The Zn atomic positions are found to be energetically more favorable doping sites than O. The Eu has a lower formation energy than Zn and O vacancies, helps in lowering the formation energy of point defects and induces spin polarization. Mg is less favorable dopant energetically and is not inducing any magnetism in the clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The stable atomic cluster has been attracted great interest recently not only as an ultimate particle with properties controlled by its shape and even size but also as the promoting possibility to reassembling it into a novel class of material structure—nanoporous crystalline polymorph—while it serves as primary building blocks. [ 7,8,41,42 ] Phases formed by this approach maybe potentially applied in atomic transports, [ 43 ] in possible forming superconducting states, [ 44,45 ] or in thermoelectric by double bubble nesting cages, [ 45,46 ] or in enhanced magnetic and optical absorption by doping with transition metal, [ 47,48 ] in photovoltaic by enhancing the separation of electron–hole pair, [ 17 ] and so on. The trend of the “magic” clusters assembling motif has continued to form the low‐dimensional phases toward tailoring properties or functionalities [ 24-26,42 ] using various structure prediction.…”
Section: Resultsmentioning
confidence: 99%
“…The stable atomic cluster has been attracted great interest recently not only as an ultimate particle with properties controlled by its shape and even size but also as the promoting possibility to reassembling it into a novel class of material structure—nanoporous crystalline polymorph—while it serves as primary building blocks. [ 7,8,41,42 ] Phases formed by this approach maybe potentially applied in atomic transports, [ 43 ] in possible forming superconducting states, [ 44,45 ] or in thermoelectric by double bubble nesting cages, [ 45,46 ] or in enhanced magnetic and optical absorption by doping with transition metal, [ 47,48 ] in photovoltaic by enhancing the separation of electron–hole pair, [ 17 ] and so on. The trend of the “magic” clusters assembling motif has continued to form the low‐dimensional phases toward tailoring properties or functionalities [ 24-26,42 ] using various structure prediction.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a ZnO cluster with 12 oxygen or zinc atoms was used, as reported by other researchers [31][32][33]. The (ZnO) 12 cluster is used because it has a stable geometry with a cage-like structure, and as a results, the (ZnO) 12 cluster geometry is a good precursor for studying doped-ZnO [29].…”
Section: The Optimized Geometrymentioning
confidence: 99%
“…Transition metal oxide clusters and in particular late transition metal oxide clusters of 3d elements are least understood due to their complicated electronic structure and the large number of competing atomic structures. In recent times, various transition metal oxide clusters such as FeO, [1][2][3][4] NiO, 5,6 CoO, 7,8 ZnO, [9][10][11] etc. have been investigated to understand their role in the field of catalysis, supercapacitors, semiconductors, fuel cells, sensors, etc.…”
Section: Introductionmentioning
confidence: 99%